Combining field methods and numerical modelling to address challenges in characterising discontinuity persistence and intact rock bridges in large open pit slopes - Tuckey, Z.; Stead, D.; Eberhardt, E. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Confidence in stability assessments of large rock slopes may be improved by greater understanding the persistence of adverse discontinuities, and the proportion and location of intact rock bridge content within the slope. This paper presents a discussion of the challenges and uncertainty in characterising discontinuity persistence and intact rock bridges, with reference to results from field investigations of open pit slopes at three mines using digital photogrammetry, ground-based LiDAR, and modified 2D window mapping methods. A conceptual numerical model is then devised, where a distinct element numerical code was applied to investigate the influence of rock bridges on brittle rock mass failure and dilation in a model large open pit slope. Distinction between co-planar or out-of-plane intact rock bridges, and larger ‘rock mass bridges’ between more persistent discontinuities is considered necessary and the authors suggest that a fracture network engineering approach tailored to large open pits may be helpful for their characterisation. With modified trace mapping procedures, intact rock bridges may be quantified in terms of an intensity parameter R21 that describes the total length of inferred rock bridge traces per unit area within a mapping window. An analogous blast-induced damage intensity factor B21 is also introduced, that describes the total length of blast-induced fracture traces per unit area in a mapping window. For numerical models, a damage intensity parameter D21 is applied, which quantifies the intensity of fracturing that develops inside a modelled slope.